Toxic Masculinity in Short Stories: The Black Cat’ and the Tell-Tale Heart - Arini, Putri Syahara; Nirmalawati, Widya (Journal of English Language and Education, 2025)
Toxic masculinity is a manifestation of excessive masculine dominance, including violence, aggression, and suppression of emotions. This study analyses how toxic masculinity is reflected in two of Edgar Allan Poe's short stories, The Black Cat (1845) and The Tell-Tale Heart (1843). Using a qualitative approach and R. W. Connell's theory of hegemonic masculinity, this study reveals that toxic masculinity in both stories is seen through aggressive domination, violence against weak groups, and the failure of the main characters to manage their emotions. In The Black Cat, toxic masculinity manifests through violence against animals and his wife, fuelled by alcoholism. Meanwhile, in The Tell-Tale Heart, the physical domination of an old man reflects the need to assert power. This research demonstrates the relevance of this phenomenon to the challenges of modern society and recommends interdisciplinary analyses to deepen the understanding of the impact of toxic masculinity on social relationships.